THE EFFECT OF INTERNAL SERVICE QUALITY (INSERVQUAL) ON CONSUMER SERVICE BEHAVIOR (Study on employee PT. Bank Pembangunan Daerah Jawa Timur Tbk branch Blitar) - Agus Purnomo; Noer mijati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Purpose - This research is to examine the effect of Internal Service Quality on Customer Service Behavior at Bank Jatim branch Blitar. In order to know the relationship occur among the independent variables Internal Service Quality (Reliability, Assurance, Tangible, Emphaty, and Responsiveness) on Customer Service Behavior the regression analysis, F test and t test was conducted. Design/Population/Metodology - This research is explanatory research, in accordance with its purpose to explain the correlation and relations of some fixed variables.The population of this research was the employee of Bank Jatim branch Blitar. The research using cencus, a study by all element human resource/employee in bank jatim branch blitar and the research instruments was tested use the validity test, reliability test and classical assumption test. The hypothesis testing was using the Ftable and t table to analyze the data to be used in Multiple Regression Analysis. Result - The multiple regression showed that, simultaneously, Internal Service Quality (Reliability, Assurance, Tangible, Emphaty, and Responsiveness) had significant effect on Consumer Service Behavior. While partially tested, the variables of Reliability, Assurance and Emphaty had significant effect on Consumer Service Behavior. Then, Tangible and Responsiveness had not significant effect on Consumer Service Behavior. While dominant test shows Assurance has a dominant effect on Consumer Service Behavior. Keywords: customer service behavior, internal service quality, internal marketing